GENERAL PARKING FEE MODEL ON BUS TERMINAL FOR PRIVATE OWNER (Perner's Contacts, 2010)
This article deals with the summary of the problems of developing the general model (generalized consecution) of parking fee on bus terminals of private operators/owners.
Keywords: Model; generalized modeling; parking fee; bus terminal